Decision-making style profiles of pre-service biology teachers in socio-scientific issues - Marlina Ummas Genisa; Bambang Subali; Djukri Djukri; Habibi Habibi (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study aimed to describe the decision-making style regarding the socio-scientific issue (SSI) of pre-service Biology teachers in four regions of Indonesia as a guide in designing active, varied, and creative learning involving students in each learning session. Data were collected using a questionnaire to 514 participants and analyzed descriptively-quantitatively. The results showed that each student's decision-making style is influenced by cognitive dimensions and processes during learning. Analytical decision-making styles also have a positive effect on gender, grade, region, and university.